Morphology‐controlled synthesis and structural features of ultrafine nanoparticles of Co3O4: An active electrode material for a supercapacitor. Issue 4 (15th July 2022) - Shwetha, Kollur Prabhakarrao; Manjunatha, Channegowda; Sudha Kamath, Mangalore Krishna; Vinaykumar,; Radhika, Mallesara Ganesh Rao; Khosla, Ajit
Abstract: In this study, the authors present a morphology‐controlled synthesis strategy for the preparation of Co3 O4 nanoparticles. The importance of the fuel (ascorbic acid) to oxidiser (cobalt nitrate) ratio (F/O ratio) in obtaining evenly distributed nanoscale grain Co3 O4 with pure crystalline phases using the solution combustion method is proposed. The structural features of all the as‐formed cobalt oxide nanoparticles were studied using the powder X‐ray diffraction technique, a field emission scanning electron microscope and Raman spectroscopic techniques. The electrochemical characteristics of all the as‐formed cobalt oxide nanoparticle‐embedded electrodes were examined by cyclic voltammetry, galvanostatic charge–discharge studies and electrochemical impedance spectroscopy in a 2 M KOH solution. The electrochemical data demonstrated that the Co3 O4 nanoparticles showed good capacitive behaviour. The morphological changes in the Co3 O4 nanoparticles affect the charge storage mechanism, and Co3 O4 nanoparticles with an F/O ratio equal to 1 (COO2) showed the highest electrochemical property, with a specific capacitance of 166 F g −1 at a current density 0.5 A g −1 . The COO2 electrode material showed capacitance retention of 90% after 5000 cycles. Abstract : The morphological changes in the Co3 O4 nanoparticles affect the charge storage mechanism, and Co3 O4 nanoparticles with an F/O (fuel to oxidiser) ratio equal to 1 showed the highest electrochemical property, with a specific capacitance of 166 F g −1 at a current density 0.5 A g −1 . The COO2 electrode material showed capacitance retention of 90% after 5000 cycles.